2018
DOI: 10.1007/s11136-018-1782-y
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties of depression questionnaires in patients with diabetes: a systematic review

Abstract: PurposeTo conduct a systematic review on measurement properties of questionnaires measuring depressive symptoms in adult patients with type 1 or type 2 diabetes.MethodsA systematic review of the literature in MEDLINE, EMbase and PsycINFO was performed. Full text, original articles, published in any language up to October 2016 were included. Eligibility for inclusion was independently assessed by three reviewers who worked in pairs. Methodological quality of the studies was evaluated by two independent reviewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 61 publications
1
29
1
Order By: Relevance
“… 66 The properties of various screening instruments and their validities in T2DM remain an ongoing area of study. 67 Differential item functioning is one analysis that can be used to determine whether the questions on each are non-invariant with respect to T2DM and/or T2DM characteristics to ensure that they accurately measure depressive symptoms rather than symptoms of T2DM. 68 , 69 Self-report screening questionnaires used in T2DM include the following: the CES-D, 46 Beck Depression Inventory (BDI), 70 World Health Organization (WHO) Well-Being Index, 71 PHQ, 72 and Edinburg Depression Scale (EDS), among others.…”
Section: Depression Screening and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“… 66 The properties of various screening instruments and their validities in T2DM remain an ongoing area of study. 67 Differential item functioning is one analysis that can be used to determine whether the questions on each are non-invariant with respect to T2DM and/or T2DM characteristics to ensure that they accurately measure depressive symptoms rather than symptoms of T2DM. 68 , 69 Self-report screening questionnaires used in T2DM include the following: the CES-D, 46 Beck Depression Inventory (BDI), 70 World Health Organization (WHO) Well-Being Index, 71 PHQ, 72 and Edinburg Depression Scale (EDS), among others.…”
Section: Depression Screening and Diagnosismentioning
confidence: 99%
“…68 , 69 Self-report screening questionnaires used in T2DM include the following: the CES-D, 46 Beck Depression Inventory (BDI), 70 World Health Organization (WHO) Well-Being Index, 71 PHQ, 72 and Edinburg Depression Scale (EDS), among others. 67 The self-report scales used most commonly in T2DM, and studies assessing their validity, have been reviewed recently. 67 …”
Section: Depression Screening and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…While we did not have the ability to fully characterize the presence of metabolic syndrome, given the relatively high percentage of diabetes, hypertension, and obesity in this cohort, it is likely that a large percentage of the patients had metabolic syndrome. 28 In T2DM, the comorbidity of depressive symptoms and of major depression is associated with poorer clinical management and poorer outcomes than either alone 29 ; the same pattern is found for coincident depression and HF. 7 We found that T2DM patients specifically had more somatic/affective depressive symptoms but not cognitive Mechanistically, we found that sST2, IL-6, BNP, and poor sleep quality were independent predictors of somatic/affective depression while BMI, type of cardiac dysfunction, and medications were not.…”
Section: Discussionmentioning
confidence: 88%
“…Unfortunately, patients' depression is not frequently identified in routine clinical care ( 47 , 48 ). Multiple instruments have been developed to identify depression in research and in clinical practice ( 49 ).…”
Section: The a To Z List For Managing Type 2 Diabetes In Culturally Dmentioning
confidence: 99%